The Pregnancy Environment and Lifestyle Study (PETALS): a population-based longitudinal multi-racial birth cohort - Yeyi Zhu; Monique M. Hedderson; Juanran Feng; Ashley A. Mevi; Assiamira Ferrara (BMC, 2017)
Abstract Background Increasing recognition has been received regarding the proven and suggested links between multi-level environmental exposures on a broad scale (e.g., chemical, clinical, behavioral, physical and social) and health deficits originated from the critical window of development. However, such prospective human data are limited. In 2016, the National Institutes of Health funded 35 centers comprising 84 extant cohorts for the Environmental Influences on Child Health Outcomes (ECHO) pediatric cohorts program. The Pregnancy Environment and Lifestyle Study (PETALS) is one of the cohorts at the participating centers of Kaiser Permanente Northern California (KPNC). Methods PETALS was originally funded by the National Institute of Environmental Health Sciences to establish a longitudinal birth cohort of 3,350 mother-infant pairs and conduct a nested case-control study of 300 women with gestational diabetes (GDM) and 600 matched controls to investigate the associations between phenol exposures in first and second trimesters and GDM risk and the related outcome of infant macrosomia. This paper describes the prospective cohort design of PETALS, current research activities, and cohort profile of enrolled women who delivered as of February 2016. Women are enrolled from the KPNC membership. Fasting blood draw, urine collection, anthropometric measurements, and questionnaires on health history and lifestyle are completed at baseline and follow-up clinic visits with targeted windows of 10-13 and 16-19 weeks of gestation, respectively. Further, women's clinical and health assessments before and after the index pregnancy in addition to their children's birth outcomes and health information can be abstracted from electronic health records, allowing future follow-up. Study data could also be linked and extended to a myriad of additional observational data including environmental and area-level databases and census data. Discussion In this racially- and ethnically-diverse pregnancy cohort, the generated biospecimen and data repository will establish a comprehensive framework which may provide unique opportunities to address a multitude of research questions on the intrauterine environment and adverse pregnancy and birth outcomes in a representative multi-racial/ethnic population with generalizable findings.